Introduction - Bussotti, Luca (2015)
This e-book is the result of a panel organized in the Fifth European Congress of African Studies (ECAS 5) that took place in Lisbon in June 2013. We thought of organizing this panel on “Press Freedom and Right to Information in Africa” since the question of freedom, especially press freedom, is presently extremely important in all African countries. However, it is not yet well known, both in the academic context and by the public. With rare exceptions (Cape Verde can represent this category, in the group of countries analyzed in this e-book), all African countries are ranked low according to the international index of press freedom. The majority of them (such as Eritrea, Equatorial Guinea, Sudan) occupies the last positions in this international index.